Anatomy and physiology of the eye (with clinical correlation): textbook : [for bilingual education students specializing in "General Medicine" (31.05.01) and "Dentistry" (060105)]Анатомия и физиология глаза (с клиническими примерами): учебное пособие : [для студентов билингвального обучения по специальности «Лечебное дело» (31.05.01) и «Стоматология» (060105)] - Филиппова, Е. О. офтальмология 19880902 Екатерина Олеговна (Издательство СибГМУ, 2023)
The textbook covers the development of the eyeball, provides a detailed description of the microscopic structure of the eye and its accessory apparatus, and thoroughly explains the blood supply and innervation of the visual organ. Clinically significant aspects of eye anatomy, histology, and physiology are presented. The textbook is written in accordance with the federal state educational standard of higher professional education approved by the Ministry of Health of the Russian Federation in 2010 and is intended for bilingual education students specializing in «General Medicine» (31.05.01) and «Dentistry» (060105).